Emerging trends in the recovery of ferrospheres and plerospheres from coal fly ash waste and their emerging applications in environmental cleanup - Yadav, Virendra Kumar; Modi, Timsi; Alyami, Abeer Yousef; Gacem, Amel; Choudhary, Nisha; Yadav, Krishna Kumar; Inwati, Gajendra Kumar; Wanale, Shivraj Gangadhar; Abbas, Mohamed; Ji, Min-Kyu; Jeon, Byong-Hun (Frontiers in Earth Science, 2023)
Coal fly ash (CFA) is one of the major global problems due to its production in huge volumes. Fly ash has numerous toxic heavy metals which it is considered hazardous material. But it has several value-added minerals like ferrous, alumina, and silica along with other minerals. Fly ash also has several natural micros to nanostructured materials, for instance, spherical ferrous-rich particles, cenospheres, plerospheres, carbon nanomaterials, and unburned soot. These microns to nanosized particles are formed from the molten slag of the coal, followed by condensation. Out of all, plerospheres which are hollow spherical particles, and ferrospheres which are ferrous-rich particles have found potential applications in the environmental cleanup, research, catalytic industries, and glass and ceramics industries. Besides this, these particles could be further surface-functionalized or will be purified for their applications. Moreover, these particles are widely explored for their potential in the army and other defense systems like lightweight materials, sensing, etc. The recovery of such particles from waste fly ash will make the process and remediation technology economical and environment friendly. The current review focuses on the various structural and elemental properties of the ferrospheres and plerospheres from the fly ash. This review also focuses on the emerging applications of both naturally formed materials in the CFA.